Bitter taste receptor (TAS2R) 46 in human skeletal muscle: expression and activity - Talmon, Maria; Massara, Erika; Quaregna, Martina; De Battisti, Marta; Boccafoschi, Francesca; Lecchi, Giulia; Puppo, Federico; Bettega Cajandab, Michele A.; Salamone, Stefano; Bovio, Enrica; Boldorini, Renzo; Riva, Beatrice; et al. (Frontiers in Pharmacology, 2023)
Bitter taste receptors are involved not only in taste perception but in various physiological functions as their anatomical location is not restricted to the gustatory system. We previously demonstrated expression and activity of the subtype hTAS2R46 in human airway smooth muscle and bronchoepithelial cells, and here we show its expression and functionality in human skeletal muscle cells. Three different cellular models were used: micro-dissected human skeletal tissues, human myoblasts/myotubes and human skeletal muscle cells differentiated from urine stem cells of healthy donors. We used qPCR, immunohistochemistry and immunofluorescence analysis to evaluate gene and protein hTAS2R46 expression. In order to explore receptor activity, cells were incubated with the specific bitter ligands absinthin and 3ß-hydroxydihydrocostunolide, and calcium oscillation and relaxation were evaluated by calcium imaging and collagen assay, respectively, after a cholinergic stimulus. We show, for the first time, experimentally the presence and functionality of a type 2 bitter receptor in human skeletal muscle cells. Given the tendentially protective role of the bitter receptors starting from the oral cavity and following also in the other ectopic sites, and given its expression already at the myoblast level, we hypothesize that the bitter receptor can play an important role in the development, maintenance and in the protection of muscle tissue functions.